2003
DOI: 10.1007/s00122-003-1210-7
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis of genetic variability in New Guinea impatiens

Abstract: New Guinea impatiens ( Impatiens hawkeri) is an economically important floral crop, however, little work has been conducted to further our understanding of the genetics of this crop. In this study, we used amplified fragment length polymorphism (AFLP) technology to investigate the level of polymorphism present among 41 commercial cultivars of New Guinea impatiens, study their genetic relatedness, and assess the genetic diversity in this material. An efficient DNA extraction protocol was developed, and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
5
16
1
Order By: Relevance
“…Lyerly, unpublished data). Generally, these studies show that genetic marker data agree with available pedigree data (Carr et al, 2003).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Lyerly, unpublished data). Generally, these studies show that genetic marker data agree with available pedigree data (Carr et al, 2003).…”
supporting
confidence: 58%
“…Other AFLP studies (Carr et al, 2003;Han et al, 2000) have focused on scoring a large number of polymorphisms to explain expected relatedness. However, this study shows that it is the quality as well as quantity of information that the polymorphisms contain, and not the quantity of polymorphisms themselves, which explains relationships and creates AFLP fi ngerprints.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years DNA markers have provided the tools needed to do this (Tomkins et al 2001). The multilocus amplified fragment length polymorphism (AFLP) DNA fingerprinting technique (Vos et al 1995) has been widely used to study genetic relationships within and among many different plant species (Hill et al 1996;Maughan et al 1996;Sharma et al 1996;Hongtrakul et al 1997;Paul et al 1997;Cervera et al 1998;Angiolillo et al 1999;Barcaccia et al 1999;Leus et al 2000;Tomkins et al 2001;Van Huylenbroeck et al 2001;Carr et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We can also rule out (ii) as a causal factor because we strictly bagged all the panicles of Jijing88 after emasculation and grew all the plants in an isolated greenhouse. Moreover, seed or pollen contamination would be a 100 and 50 % contamination, respectively, for the polymorphic loci between Jijing88 and the contaminator; both Simple Sequence Repeats (SSR) and Amplified Fragment Length Polymorphisms (AFLP) molecular marker (Carr et al 2003) analysis revealed no evidence of this (primers listed in Tables S5, S6). In addition, whole-genome resequencing revealed that none of the 202 retrotransposon loci were missing in X9 when compared to Jijing88.…”
Section: Pollination By Zizania As the Underlying Cause For The Mobilmentioning
confidence: 99%